Association between exposure to air pollutants and hospitalization for SARS-Cov-2: an ecological time-series study - Ribeiro, Paola Cristina [UNESP]; da Cunha, Cristóvão José Dias [UNESP]; Dos Santos, Adriana de Oliveira Ribeiro [UNESP]; Lucarevschi, Bianca Rezende [UNESP]; César, Ana Cristina Gobbo [UNESP]; Nascimento, Luiz Fernando Costa [UNESP] (FapUNIFESP (SciELO), 2023)
BACKGROUND: Exposure to air pollutants and illness by severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) infection can cause serious pulmonary impairment. OBJECTIVE: To identify a possible association between exposure to air pollutants and hospitalizations due to SARS-Cov-2. DESIGN AND SETTING: Ecological time-series study carried out in Taubaté, Tremembé, and Pindamon-hangaba in 2020 and 2021. METHODS: Study with Sars-Cov-2 hospitalizations with information on hospitalization date, sex and age of the subjects, duration of hospitalization, type of discharge, and costs of these hospitalizations. Statistical analysis was performed through a negative binomial regression, with data on pollutant concentrations, temperature, air relative humidity, and hospitalization date. Coefficients obtained by the analysis were transformed into relative risk for hospitalization, which estimated hospitalizations excess according to an increase in pollutant concentrations. RESULTS: There were 1,300 hospitalizations and 368 deaths, with a predominance of men (61.7%). These data represent an incidence rate of 250.4 per 100,000 inhabitants and 28.4% hospital lethality. Significant exposure (P value < 0.05) occurred seven days before hospital admission (lag 7) for nitrogen dioxide (NO2) (relative risk, RR = 1.0124) and two days before hospital admission for PM2.5 (RR = 1.0216). A 10 μg/m3 in NO2 concentration would decrease by 320 hospitalizations and » US $ 240,000 in costs; a 5 μg/m3 in PM2.5 concentration would decrease by 278 hospitalizations and » US $ 190,000 in costs. CONCLUSION: An association between exposure to air pollutants and hospital admission due to Sars-Cov-2 was observed with excess hospitalization and costs for the Brazilian public health system.
Keywords: 2019 novel coronavirus; Air pollutants; Costs; Fine particulate matter; Nitrogen dioxide; SARS-Cov-2